Pengaruh Pijat Bayi Terhadap Millestone Bayi - Suryanti; Rita Kirana; Vonny Khresna Dewi; Rusmilawaty (Sekolah Tinggi Ilmu Kesehatan Panca Bhakti, 2025)
The infancy process is a golden period in the achievement of child development that requires special attention and treatment. Child development disorders have a prevalence of 7,512.6 per 100,000 children (7.51%). Millestone is the achievement of child development. â€œThe Effect of Infant Massage on Infant Millestone at Massage House â€œGASâ€ with experimental squasi research method. In analyzing bivariate data, data were tested using the T test. The difference between the two measurements must be normally distributed, with the Shapiro-Wilk Test and the results obtained Sign. 001. The results of Millestone infants before and after infant massage showed a p value of 0.000 with a significant correlation value of 0.949. In babies who were not massaged, the Mean showed a result of 1.50 and babies who were given massage was 7.33. The significant difference in infant milestone was between the group of infants who were given massage and those who were not given massage, which amounted to 5.833. The effect of infant massage on infant milestone in Massage House â€œGASâ€ Banjarbaru City Region in 2024 (p-value = 0.000).